THE SOCIALIZATION OF INDONESIAN CULTURE TO INTERNASIONAL STUDENT OF ISTANBUL SABAHATTIN ZAIM UNIVERISTY AS INTERNASIONAL COMMUNITY SERVICE - Jaziela Huwaida; Riza Ashari; Andi Nur Fadhila Mahdiyah; Nouval Salman; Jaudat Iqbal Harris (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
The lack of insight of international students in the knowledge of Indonesian culture is one of the objectives of the implementation of the Indonesian culture event. Because the many Indonesian students in Istanbul Sabahattin Zaim Univeristy is not the first support for international students to know Indonesian culture due to the busy class schedule. Whereas, Indonesia has a diversity of cultures which can be an opportunity for Indonesian students to introduce their culture to international students. The Indonesian culture event uses direct method and role-play to apply cultural introduction to international students. And the results of interviews from international students stated that they were very enthusiastic about the Indonesian culture event, this received good feedback for both sides, both in terms of the Turkish International KKN team and Istanbul Sabahattin Zaim Univeristy.